Pollination by the locally endangered island flying fox (Pteropus hypomelanus) enhances fruit production of the economically important durian (Durio zibethinus). Issue 21 (18th September 2017) - Aziz, Sheema A.; Clements, Gopalasamy R.; McConkey, Kim R.; Sritongchuay, Tuanjit; Pathil, Saifful; Abu Yazid, Muhammad Nur Hafizi; Campos‐Arceiz, Ahimsa; Forget, Pierre‐Michel; Bumrungsri, Sara
Abstract: Fruit bats provide valuable pollination services to humans through a unique coevolutionary relationship with chiropterophilous plants. However, chiropterophily in the Old World and the pollination roles of large bats, such as flying foxes ( Pteropus spp., Acerodon spp., Desmalopex spp.), are still poorly understood and require further elucidation. Efforts to protect these bats have been hampered by a lack of basic quantitative information on their role as ecosystem service providers. Here, we investigate the role of the locally endangered island flying fox Pteropus hypomelanus in the pollination ecology of durian ( Durio zibethinus ), an economically important crop in Southeast Asia. On Tioman Island, Peninsular Malaysia, we deployed 19 stations of paired infrared camera and video traps across varying heights at four individual flowering trees in a durian orchard. We detected at least nine species of animal visitors, but only bats had mutualistic interactions with durian flowers. There was a clear vertical stratification in the feeding niches of flying foxes and nectar bats, with flying foxes feeding at greater heights in the trees. Flying foxes had a positive effect on mature fruit set and therefore serve as important pollinators for durian trees. As such, semi‐wild durian trees—particularly tall ones—may be dependent on flying foxes for enhancing reproductive success. Our study is the first to quantify the role of flying foxes in durian pollination, demonstrating that these giant fruit bats may have far more important ecological, evolutionary, and economic roles than previously thought. This has important implications and can aid efforts to promote flying fox conservation, especially in Southeast Asian countries. Abstract : Camera‐trapping shows that flying foxes ( Pteropus hypomelanus ) contribute to reproductive success of the durian ( Durio zibethinus ) tree. This new evidence of chiropterophily in the Palaeotropics shows how large fruit bats can also play a role in the production of economically important fruit.